The Impact of Renewable Energy Consumption and Economic Growth on Environmental Degradation in Somalia - Mohamud, Iqra Hassan; Mohamud, Ahmed Abdirashid (International Journal of Energy Economics and Policy, 2023)
This study investigates the impact of renewable energy consumption and economic growth on environmental degradation in Somalia between the period 1990-2020. Econometric tools ARDL and Pairwise Granger Causality Test were used. A stationarity test was first carried out to ascertain the stationarity and all variables are all integrated of order (0) and (I). Results from the short term demonstrate a positive, significant relationship between renewable energy usage, oil price, and environmental deterioration, and a negative, significant relationship between foreign direct investment (FDI), population, and environmental degradation. More so, in the short term, there is a positive and insignificant relationship between economic growth and environmental degradation. while the long-run result revealed a positive, significant relationship between FDI, population, oil price, and environmental degradation, as well as a negative, significant relationship between the use of renewable energy, economic growth, and environmental degradation. Results indicate that renewable energy consumption is a key contributor to environmental degradation in both short and long-run periods in Somalia. The result from the Granger causality test revealed that there is unidirectional causality from EG to ED, REC to ED, ED to FDI, and FDI to EG of Somalia.